Integrating 21st Century Skills into the Islamic Boarding School Curriculum to Improve Student Competence in the Global Era - Husairi Husairi (Al-Munawwarah: Journal of Islamic Education, 2025)
Islamic boarding schools (pesantren) have long sustained moral formation and classical Islamic scholarship, yet rapid digital transformation and shifting labor-market demands require santri to develop 21st‑century competencies alongside religious mastery. This study aims to analyze strategies for integrating 21st‑century skills into the pesantren curriculum without eroding pesantren identity, using Pesantren Al‑Yasini as a case. A qualitative case-study design was employed, drawing on participant observation, in-depth interviews with pesantren leaders, teachers, students, and alumni, and analysis of curriculum and policy documents. The findings show a shared recognition of the urgency of strengthening critical thinking, communication, collaboration, creativity, and digital literacy. Integration is most feasible when these competencies are mapped into learning outcomes, content, pedagogy, and assessment, and operationalized through value-guided technology use, hybrid learning routines, and project-based activities (e.g., sharia entrepreneurship and leadership projects). Key enabling factors include leadership commitment, teacher readiness, and curriculum flexibility, while constraints include uneven infrastructure and resistance to pedagogical change. The study concludes that a staged, value-based integration model can enhance santri competitiveness while preserving the pesantren’s core mission. This research contributes an empirically grounded framework to inform curriculum development and policy support for pesantren in the digital era.